IMPLEMENTATION OF SOCIAL AND ENVIRONMENTAL RESPONSIBILITY INDIVIDUAL COMPANY - Nabila Azzahra; Disriani Latifah Soroinda (Universitas Labuhanbatu, 2024)
Individual companies exist because of the issuance of Law Number 11 of 2020 concerning Job Creation. The regulations added to the Limited Liability Company Law mean that all provisions contained therein also apply to individual companies as long as there are no special or excluded regulations, including regarding social and environmental responsibility. The problem arises regarding whether the scope of social and environmental responsibility also covers individual companies, which causes individual companies to be obliged to carry out social and environmental responsibilities and what kind of individual companies are obliged to do so. The research method used is a doctrinal method, through an approach to statutory regulations and concepts in law. The results obtained in this research show that individual companies are obliged to carry out social and environmental responsibilities as long as they meet the existing criteria and provisions. Apart from providing benefits to local people and communities, there are also benefits that companies obtain from carrying out social and environmental responsibilities, thus enabling individual companies to also have the urgency to get involved voluntarily. Considering the differences between Limited Liability Companies and Individual Companies, more specific regulations are needed regarding the implementation and supervision of the implementation of Social and Environmental Responsibility.Keywords: Social; environmental; responsibility; individual companies